William Hasker’s avoidance of the problems of evil and God (or: on looking outside the igloo) - Phillips, D. Z. (International journal for philosophy of religion, 2007)
Our Book Review Editor, James Keller, invited William Hasker to write a review of the Book by D.Z. Phillips, The Problem of Evil and the Problem of God and then in consultation with the Editor-in-Chief invited Phillips to respond. Aware of both their respect for each other and their philosophical differences we planned that Hasker’s review and Phillips’ response would appear in the same issue of the International Journal for Philosophy of Religion. Unfortunately that was not to be. Dewi, as he was known to his many friends throughout the world, collapsed at his desk on 25 July, 2006 in the library of his beloved University of Wales, Swansea. Although we were not able to have the review and response appear in the same issue as we had all planned, we are now printing his response to Hasker’s review, “D.Z. Phillips’s Problems with Evil and with God,” which appeared in IJPR, Vol. 61,3. Dewi had completed the review and thanks to the efforts of Helen Baldwin who prepared the manuscript and Dewi’s wife, Monica, and family we are able to print it here. Since Dewi was responding to an earlier version of Hasker’s review, a few minor editorial changes have been made. Dewi’s death is a great loss to the philosophical community and a deep personal loss to his family and friends, but I am confident that he would be pleased to have this response appear. He might even have a story to tell, a comment that those who knew him well will fully understand. Eugene Thomas Long.